Reduced levels of circulating natural killer cells in children with celiac disease - Mehmet Agin; Eylem Sevinc; Erkan Dogan; Nergiz Sevinc (Indonesian Pediatric Society Publishing House, 2020)
Background Celiac disease (CD) is an autoimmune disease characterized by malabsorption. Serologic testing for CD consists of Ig A type of antitissue transglutaminase (tTG), antiendomysium (EMA). These tests are helpful in monitoring adherence to the gluten-free diet (GFD). Natural killer (NK) cell count alterations have been reported in various diseases, such as cancer, Crohn's disease, malnutrition, and autoimmune disorders. Objective To compare peripheral blood NK cell counts in children with celiac disease (CD) to healthy controls. The second aim was to analyze for possible correlations between NK cells (CD3-/CD16+, CD56+) and tissue transglutaminase (tTG)-IgA and tTG-IgG, as well as endomysial antibody EMA-IgA indicating gluten sensitivity. Methods Fifty children with CD were compared to 48 healthy children as controls, with similar age and sex distribution. Peripheral blood NK cell counts were measured by flow cytometry. Results The median (P25-P75) ages of the 50 celiac patients (23 male; 46%) and 48 controls (21 male; 44%) were 10 (2-17) years and 9 (3-17) years, respectively. Mean follow-up duration was 3 years, ranging from 1-10 years. All CD patients had positive tTG-IgA and EMA-IgA tests while it was negative in all (100 %) control patients. The absolute number of circulating CD16+ NK cells (259.52 vs. 1404.36 μ/L) and CD56+ NK cells (366.24 vs. 2440.46 μ/L) were significantly lower in the celiac group than the control group (P<0.05 for both). The absolute numbers of circulating white blood cells (7785 vs. 8165 μ/L) and lymphocytes (3106 vs. 3173 μ/L) were not significantly different between the celiac and control groups (P>0.05 for both). Correlation analysis between the absolute number of circulating NK cells and tTG-IgA, tTG-IgG, and EMA-IgA levels in CD patients revealed no significant relationships (P>0.05 for all). Conclusions Peripheral blood NK cell count were significantly lower in celiac patients than controls, hence, decreased NK cell counts may be an abnormal feature seen in autoimmune diseases. NK cell count in celiac patients had no significant correlations to tTG-IgA, tTG-IgG, or EMA-IgA levels. Therefore,  NK cell count  may be inappropriate marker for monitoring compliance to a gluten free diet.